1969
DOI: 10.1002/1097-0142(196907)24:1<92::aid-cncr2820240113>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Spermatocytic seminoma.I. Clinicopathologic study of six cases and review of the literature

Abstract: Six cases of spermatocytic seminoma are reported, and the literature on the subject is reviewed. This neoplasm occurs in elderly persons, is grossly characterized by a gelatinous appearance, and has distinctive microscopic characteristics. Its degree of differentiation is far greater than that exhibited by classical seminoma, a tumor from which it should be separated. It is exclusively limited to the testicle and is never associated with teratomatous elements. Claims that it has a less favorable prognosis than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

1969
1969
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 10 publications
1
38
0
5
Order By: Relevance
“…In addition, the size of the germ cells varied, ranging from cells with small hyperchromatic nuclei to large blastic cells with vesicular nuclei. In that respect, the nuclear variations in the germ cell component in our case had some similarities to nuclear variations seen in spermatocytic seminomas [30]. Atypical mitoses in germ cells present in two of the three testicular cases are another argument supporting their neoplastic nature.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the size of the germ cells varied, ranging from cells with small hyperchromatic nuclei to large blastic cells with vesicular nuclei. In that respect, the nuclear variations in the germ cell component in our case had some similarities to nuclear variations seen in spermatocytic seminomas [30]. Atypical mitoses in germ cells present in two of the three testicular cases are another argument supporting their neoplastic nature.…”
Section: Discussionsupporting
confidence: 71%
“…It is also the sole germ cell tumour that always occurs in pure form and is not admixed with other neoplastic germ cell elements, including seminoma. Spermatocytic seminoma may be confused with classical seminoma; the distinction is important from the clinical standpoint because spermatocytic seminoma virtually never metastasises [20,29,56] and requires no treatment besides orchiectomy [7,14,33,45,47,53,57]. Recent immunohistochemical and molecular studies [42,51,59] have demonstrated a different origin for seminoma/ dysgerminoma and spermatocytic seminoma.…”
Section: Discussionmentioning
confidence: 99%
“…92,93 Spermatocytic seminoma Spermatocytic seminoma may be confused with usual seminoma, a very important distinction from the clinical standpoint since spermatocytic seminomas virtually never metastasize (except for those with a rare complication mentioned below) and do not merit treatment apart from orchiectomy. [94][95][96][97] This tumor is limited to the male gonad and has a number of fascinating aspects. Although most patients with spermatocytic seminoma are older (mean, 55 years) 98 than those with usual seminoma (mean, 40 years), 4 there is considerable overlap.…”
Section: Germinomamentioning
confidence: 99%